Order Projection of Linear Operators (مجلة البحوث الأكاديمية, 2021)
Order (or band) projections are the most important subjects in functional analysis and its applications. This paper studies a special class of positive linear operator known as order projections, and provides some of its application which are; extension theorem for linear operators, theory of order continuous operators, and the components of positive operators. A useful comparison property of order projection is described.
Keywords: order projection; Archimedean; ideal; Riesz spaces